PENDIDIKAN KEWARGANEGARAAN DAN PEMBENTUKAN PREFERENSI POLITIK AWAL PEMILIH PEMULA - Tamma, Sukri (Jurnal Politik Profetik, 2021)
This paper aims to show the important role of civic education in influencing the early political preferences of novice voters. Political preference is one of the important aspects for someone to be able to participate properly in a democratic system. Based on certain political preferences, a person will have reasons and foundations for his behavior and political choices, including novice voters. Therefore, an understanding of the aspects of its formation becomes an important aspect to be understood before being directly involved in political elections. Based on qualitative research conducted in Makassar City in 2020 on novice voters who are high school students, it was found that the formation of their initial political preferences was not only influenced by parental preferences but also through civic education courses at schools. The course which consists of standards and social values in behaving as citizens has given them an initial understanding of the importance of placing themselves well in the political space. This makes civic education space for socialization as well as political education for novice voters. This understanding then becomes the basis for developing their understanding of politics and how they should behave as good citizens in a democratic system.